Islamic financial system theory and practice - Kassim, Salina (IIUM Press, 2020)
Amid the rapid growth and increasing presence of Islamic finance industry across the globe, interests in detailed information and knowledge in Islamic banking and finance are increasing, not just by those involved in the industry for commercial reasons, but also by those who would like to have a deeper understanding of the Islamic financial system. Islamic finance now, is seen as a viable alternative to the conventional financial system, which has the prospects of high growth and application that could potentially provide the panacea to address issues and problems currently facing the conventional financial system. Since Islamic finance is growing at a rapid pace and has started to make a meaningful economic contributions in many countries, there is a growing interest on the role of Islamic finance in contributing to efficient functioning of the overall financial system and its relation to the real economic activities. The unique feature of Islamic finance which requires the compliancy to the Shariah in all its aspects, would result in an economy achieving the maqasid al-Shariah, and obtaining the noble objective of socio-economic justice for all, which is the major characteristic of an Islamic economy. This book aims to provide a comprehensive understanding about the characteristics, structure and operations of an Islamic financial system, particularly in performing its role as an integral component of the overall economic system. This involves an understanding on the foundation as well as evaluation on the concepts and structure of the Islamic financial system, as well as the legal and regulatory framework facing the system. Comparisons are made between the Islamic financial systems with its conventional counter-part so as to highlight the unique features of the Islamic financial system in mobilising financial capital in a Shariah-compliant manner, while pointing-out the economic implications of the differences between the two systems. Key principles and characteristics of the Islamic financial system, as well as the financial products or instruments traded in various segments of the system are highlighted. This includes the operations of each component of the Islamic financial system, starting from the Islamic money market, Islamic equity market, sukuk market, Islamic unit trusts industry, Islamic banking institutions, and Islamic non-bank financial institutions. Also critical to the functioning of the Islamic financial system is the monetary system, which in essence, relates the Islamic financial system to the overall economic system.